The One-Way Mirror: Law, Privacy, and the Media - Lawrence M. Friedman (Washington University Law Quarterly, 2004)
In every complex society, there have been famous people. But only in modern times do we have celebrities. Only in modern times do we have mass media; and it is the mass media that make it possible for us to be so familiar with famous people. This familiarity, as I have argued, is the essence of the celebrity. In this Article, I am going to talk about some of the social and legal consequences of this aspect of the world we live in—the world that has created, nurtured, and fostered the celebrity culture.
Keywords: Celebrities; Mass media; Right of privacy; United Kingdom; Diana; Princess of Wales